Determinant of Auditor’s Performance: Case of Government Auditor in Bali Province - Luh Komang Merawati (AIBPM Publisher, 2019)
This study aims to determine the effect of role stress moderated by healthy lifestyle and selfcompassion on the performance of government auditors in BPKP and BPK RI Representative of Bali Province in Denpasar. Role stress dimensions include role ambiguity, role conflict and role overload. Data was obtained by distributing questionnaires and analyzed using moderated regression with interaction test. The results prove that role overload, healthy lifestyle and selfcompassion has positif significant impact on the government auditor performance. Healthy lifestyle and self-compassion are able to moderate the influence of role overload on auditor performance with negative direction.